Analisis Ketidaksesuaian Batas Usia Dewasa dan Konflik Normatif Antara Hukum Pidana Materiil dan Hukum Perdata di Indonesia (Studi Putusan Kasasi Nomor 897 K/PID/2019) - Manggin, Manggin; Khutub, Muhammad (Universitas Ekasakti, 2023)
Determining the age limit for adulthood is a critical factor in determining the validity of legal actions, reflecting an individual's skills in carrying out legal actions. This article investigates legal proficiency regulations in Indonesia, highlighting the ambiguity in the assessment of adulthood that creates dilemmas, especially in Article 332 Paragraph (1) of the Criminal Code. As a case study, the analysis was carried out on the Rusly Yaprin Kalo case, which had an impact on the complexity of the concept of adulthood and differences in interpretation between criminal and civil law. This research applies a normative and qualitative juridical approach, exploring various regulations governing the age limit of adulthood in Indonesia and producing an in-depth understanding of potential conflicts between criminal and civil law. The results highlight discrepancies in adult age limits that may impact law enforcement and speak to the need for harmonization of relevant laws.